A Dual-Signal Ratiometric Optical Sensor Based on Natural Pine Wood and Platinum(II) Octaethylporphyrin with High Performance for Oxygen Detection - Zhongxing Zhang; Yujie Niu; Hongbo Mu; Jingkui Li; Jinxin Wang; Ting Liu (Sensors)
Optical oxygen sensors have attracted considerable attention owing to their high sensitivity, rapid response, and broad applicability. However, their test results may be affected by fluctuations in the pump light source and instability of the detection equipment. In this study, the intrinsic luminescence of pine wood was utilized as the reference signal, and the luminescence of platinum(II) octaethylporphyrin (PtOEP) was employed as the oxygen indication signal, to fabricate a dual-signal ratiometric oxygen sensor PtOEP/PDMS@Pine. The ratio of the luminescence of pine wood to that of PtOEP was defined as the optical parameter (OP). OP increased linearly with oxygen concentration ([O2]) in the range of 10–100 kPa, and a calibration curve was obtained. The sensor exhibits excellent anti-interference capabilities, effectively resisting fluctuations from laser sources and detection equipment. It also displays stable hydrophobicity with a contact angle of 118.3° and maintains excellent photostability under continuous illumination. The sensor exhibited long-term stability within 90 days and robust recovery performance during cyclic tests, wherein the response time and recovery time were determined to be 1.4 s and 1.7 s, respectively. Finally, the effects of temperature fluctuations and photobleaching on the sensor’s performance have been effectively corrected, enabling accurate oxygen concentration measurements in complex environments.